Isolated Posterior Instrumentation for Selected Cases of Thoracic and Lumbar Spinal Tuberculosis without Radical Debridement - Ye, Shuming; Sun, Jian; Jing, Juehua (Zeitschrift für Orthopädie und Unfallchirurgie, 2022)
Background The purpose of this study was to evaluate the clinical outcomes of thoracic and lumbar spinal tuberculosis treated with isolated posterior instrumentation without radical debridement.Methods This study retrospectively analyzed 73 patients with thoracic and lumbar spinal tuberculosis who were treated using isolated posterior instrumentation without radical debridement in our hospital between January 2012 to December 2019. The patient group was composed of 42 men and 31 women with a mean age of 67.3 ± 8.6 years. The tuberculosis spine instability score (TSIS) was used to evaluate spine stability. All patients received chemotherapy for 18 months after surgery. The time of surgery, blood loss, visual analogue score (VAS), kyphosis angle, Oswestry disability index (ODI), erythrocyte sedimentation rate (ESR), Frankel grading, SF-36 scores, and local recurrence and complications were analyzed to evaluate the efficacy of isolated posterior instrumentation surgery in the treatment of thoracic and lumbar spinal tuberculosis.Results All patients were followed up for 12 to 24 months (mean 14 ± 3.2 months). The mean surgical time was 1.2 ± 1.4 h (range, 1.2–1.6 h), and mean blood loss was 107 ± 18 mL. The postoperative symptoms were obviously relieved. The VAS, kyphosis angle, DI, and ESR decreased, respectively, from 8.24 ± 1.32, 19.82 ± 3.42, 46.25 ± 3.62, and 49.64 ± 17.61 to 1.12 ± 0.21, 7.14 ± 0.81, 20.17 ± 5.11, and 0.35 ± 1.13 at final follow-up. In comparison to preoperative values, SF-36 scores were significantly improved at final follow-up and the differences were statistically significant (p < 0.05). All patients achieved neurological recovery at the final follow-up. There were no recurrences or complications in any of the patients.Conclusion Isolated posterior instrumentation without radical debridement is a suitable minor surgical trauma that offers a remarkable advantage of effective pain relief, improvement in neurological function and performance status, and no local recurrence for selected patients with thoracic and lumbar spinal tuberculosis.
Keywords: Chemotherapie; Schuldverschreibungen; Wirbelsäulentuberkulose; Chirurgie